Pengaruh Model Project-based Learning Terhadap Sikap Berfikir Kritis yaitu Kemampuan Menganalisis, Kemampuan Pemecahan Masalah, Kemampuan Mengevaluasi - Robiul Awal; Kemas Imron Rosadi; Lukman Hakim; Aprizal Wahyudi Diprata (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2023)
This article discusses and analyzes the effect of the Project-based Learning Model on Critical Thinking, namely Analytical Ability, Problem Solving Ability, and Evaluation Ability. The method of writing this Literature Review article uses library research methods sourced from online media such as Google Scholar, Mendeley, and/or other academic online media. The results of this article are: 1) The Project-based Learning Model has an effect on Analytical Ability; 2) The Project Based Learning Model influences problem solving abilities; and 3) the Project Based Learning Model influences the ability to evaluate. In addition to these 3 exogenous variables that affect the endogenous variables of placement of subordinates, there are many other factors including Synthesizing Ability, Concluding Ability and others.